2019
DOI: 10.1111/isj.12273
|View full text |Cite
|
Sign up to set email alerts
|

Role of situational context in use continuance after critical exergaming incidents

Abstract: Use continuance is crucial in terms of information systems (IS) success. Previous research has shown that situational context can be central for IS use continuance but has paid limited attention to its specific characteristics. Furthermore, the link between situational context and use continuance has remained unexplored in the novel area of "exergames,"which are defined as digital games requiring physical effort from the player that determines the outcome of the game.Studying exergames is deemed important due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 142 publications
(232 reference statements)
0
20
0
Order By: Relevance
“…In the sixth article, Kari, Salo, and Frank () investigate the relationships between specific situational characteristics and use continuance after critical exergaming incidents. Previous research has shown that situational context can be central for IS use continuance but has paid limited attention to its specific characteristics.…”
mentioning
confidence: 99%
“…In the sixth article, Kari, Salo, and Frank () investigate the relationships between specific situational characteristics and use continuance after critical exergaming incidents. Previous research has shown that situational context can be central for IS use continuance but has paid limited attention to its specific characteristics.…”
mentioning
confidence: 99%
“…Many solutions also include gamified features [22][23] that aim to make PA more compelling and to increase the adherence of use and PA behavior. Exergames [e.g., [24][25][26][27] are games that combine PA with digital gaming. Digital wellness technologies can provide feedback regarding the user's actions in many ways.…”
Section: Digital Wellness Technology Use Among Aged Peoplementioning
confidence: 99%
“…Features for social support are another benefit (e.g., Sullivan & Lachman 2017). They can also make PA more compelling via gamification (Kari et al 2016b;Koivisto & Hamari 2019) or exergaming (e.g., Kari et al 2019;Loos & Zonneweld 2016). Moreover, digital wellness technologies can provide different feedback, which can increase the user's awareness of PA and motivate to improve related behavior (e.g., Wang et al 2016).…”
Section: Demographic Differences In the Effectiveness Ofmentioning
confidence: 99%